Evaluación de las características dinámicas en distintos suelos peruanos para la estimación de los espectros de diseño sísmico - Ortiz Salas, Carmen Eleana (2023)
Peru is located in a highly seismic zone due to the interaction between the Nazca Plate and the South American Plate, as well as the presence of surface geological faults. These seismic events have caused significant human and material losses throughout the country. Some of the most important earthquakes that have occurred in Peru include the 1966 Lima earthquake with a magnitude of 7.6 Ms, the 1970 Chimbote earthquake with a magnitude of 7.9 Mw, the 1974 Lima earthquake with a magnitude of 7.6 Ms, the 2001 Arequipa earthquake with a magnitude of 8.4 Mw, and the 2007 Pisco earthquake with a magnitude of 7.9 Mw, among other events. During these earthquakes, Peru lacked sufficient instrumentation to adequately measure these seismic events. On the other hand, determining the seismic design spectrum is crucial for the design of infrastructure projects; however, there isn't always enough information available about the parameters that affect the dynamic response of the soil, such as shear wave velocity, soil period, shear modulus, and damping. Currently, in our country, comprehensive research on this topic has not been conducted, which implies the need to define the recommended design spectrum type based on the structure's importance and the dynamic behavior of the soil. Within the scope of this research, site characterization was carried out through in-situ tests and laboratory tests. These tests allowed us to obtain profiles of shear wave velocities (Vs), profiles of compression wave velocities (Vp), predominant soil periods (T), and shear modulus and damping for small deformations. Furthermore, a comparison was made between the H/V spectral ratios obtained from microtremor measurements and accelerometer records with the H/V ratios of Rayleigh waves. Subsequently, with the information obtained from field and laboratory tests, an estimation of dynamic parameters was conducted. Additionally, shear wave velocity profiles at great depths were estimated using the Spatial Auto-Correlation (SPAC) theory. With this information, stratigraphic subsurface models were developed, including layer thicknesses and basement depth. Using the site response analysis, seismic design spectra were determined, taking into account different characteristics of the dynamic behavior of the soil for three seismic zones and three soil types (Z2-S2, Z2-S3, Z3-S3, Z4-S1, Z4-S2, Z4-S1) in accordance with the E-030 standard. The obtained results provide significant improvements in the values of TP, TL, predominant periods, and amplification coefficients of regulatory seismic design spectra used in Peruvian buildings. Additionally, the implementation of the techniques used for estimating soil dynamic properties will generate new knowledge and experiences about soil dynamic properties and propose recommendations for the E-030 and E-050 standards.